Pengaruh Anggaran Partisipasi, Budaya Organisasi, Pemahaman GCG terhadap Job Relevant Information dan Komitmen Organisasi Dampaknya Terhadap Kinerja Manajerial - Sujoko, * (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
The main objective of the study is to examined the effect of budget participation, organization culture, perception of GCG on job relevant information and organizational commitment thats impact to managerial performance. This study is to examined Goal Setting Theory, Contingency Theory, Agency Theory, and Behaviour Organization Theory. As much as 330 retail business as a sample  of this study. The result of this study show that budget participation is significant effect on job relevant information, budget participation is significant effect on organization commitment, budget participation is significant effect on managerial commitment, organization culture is significant effect on organization commitment, organization commitment is significant effect on managerial performance, organization culture is significant effect on managerial performance, perception of GCG is significant effect on job relevant information and perception of GCG is significant effect on organization commitment. Job relevant information is not significant effect on managerial performance, organization culture  is not significant effect on job relevant information and perception of GCG is not significant effect on managerial performance. Key Word :    Good Corporate Governance, Job Relevant Information, Retail Business